The Effect of Virtual Laboratory on Students' Computational Thinking on Half-Life Concepts - Mashami, Ratna Azizah; Ahmadi, Ahmadi; Hatimah, Husnul (Hydrogen: Jurnal Kependidikan Kimia, 2024)
This study investigates the impact of virtual laboratories on enhancing students' computational thinking skills, focusing on the half-life concept in radiochemistry. Utilizing a quantitative research approach, a quasi-experimental design with a one-group pretest-posttest model was employed. Thirteen students enrolled in a Radiochemistry course participated in the study. The intervention involved the use of PhET simulations as a virtual laboratory, designed to facilitate a structured and interactive learning environment. Pretest and posttest assessments were conducted to measure the students' computational thinking skills. The results showed significant improvement in computational thinking post-intervention, with notable gains in decomposition, pattern recognition, abstraction, and algorithm design. Statistical analysis using paired-sample t-test and normalized gain scores confirmed the effectiveness of the virtual laboratory in enhancing these skills. The study concludes that virtual laboratories, such as PhET simulations, are effective in developing computational thinking abilities, providing a valuable tool for modern educational practices. These findings suggest that integrating virtual laboratories into the curriculum can significantly improve students' problem-solving and critical thinking skills, preparing them for future academic and professional challenges.